The Impact of Service Quality on Guest Satisfaction - Puspitarini, Titis (Forum Kerjasama Pendidikan Tinggi, 2025)
This study examines the relationship between service quality and guest satisfaction in the hospitality industry, focusing on analyzing guest reviews from Borobudur Hotel Jakarta. Using thematic analysis, the research identifies key positive aspects, including staff friendliness, high-quality facilities, and a strategic location, significantly enhancing guest satisfaction. Conversely, recurring issues such as cleanliness concerns, service inefficiencies, and outdated facilities highlight areas for improvement. The findings demonstrate the critical role of service quality in shaping guest experiences and its direct impact on loyalty and recommendations. Strategic recommendations include enhancing cleaning protocols, optimizing service efficiency, implementing facility upgrades, and prioritizing staff training to improve customer interactions and operational workflows. This study emphasizes the interconnected nature of service quality, satisfaction, and loyalty, underscoring the need for continuous improvement to maintain competitiveness in the dynamic hospitality sector. The hotel can align its services with evolving guest expectations by addressing identified challenges and leveraging strengths, ensuring long-term success and sustained guest loyalty.